A review: An epistemological perspective of possibility of pedagogical grammar learning in community language learning method - ERNA NAWIR; Dezna Fauziah; Wenny Elsara (English Language Education Study Program, Teacher Traning and Education Faculty, Universitas Muhammadiyah Cirebon, 2023)
Given the urgency of changing the learning context caused by the current COVID-19 pandemic, learning pedagogical grammar, especially in learning English as an effort to acquire the language as a second language and or foreign language, does not only stop at the learning process which has been mostly done face-to-face directly, but can also be carried out through one alternative e-learning known as Open Learning technology-based platform. As a new atmosphere in the use of technology, especially in the field of education through the use of Massive Open Online Course (MOOC), Open Learning is an alternative of e-Learning platform that can be used as a learning medium used in the online learning process which is increasingly popular today. The methodology used by using library sources. In other words, the writers used some sources and references in getting and analyzing the data then integrated the ideas by synthesizing in drawing conclusion. The finding is by applying the Community Language Learning method for improving language skills, especially in pedagogical grammar learning, language learners can be facilitated in the learning process by making maximum use of the features of the Open Learning platform in accordance with the basic principles they have which are constructive and community-based and it is in accordance with the pattern of educational tools contained in the Open Learning philosophy itself, namely empowering students, learning concepts that are authentic, active and constructive, and focusing on building an effective educational community. Keywords: Pedagogical Grammar Learning; Community Language Learning; Open Learning Platform